2015
DOI: 10.1088/0952-4746/35/2/317
|View full text |Cite|
|
Sign up to set email alerts
|

Contaminant deposition building shielding factors for US residential structures

Abstract: This paper presents validated building shielding factors designed for contemporary US housing-stock under an idealized, yet realistic, exposure scenario from contaminant deposition on the roof and surrounding surfaces. The building shielding factors are intended for use in emergency planning and level three probabilistic risk assessments for a variety of postulated radiological events in which a realistic assessment is necessary to better understand the potential risks for accident mitigation and emergency res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The primary weather barriers selected to define these housing-units are composed of either brick-or vinyl siding for the walls with asphalt shingles for the roof. Dickson et al (2014bDickson et al ( , 2015 developed 98 housingunit models of varying combinations of nine primary weather barriers; five representing exterior walls, four representing roofs. Findings demonstrated that despite differing primary weather barrier compositions, the amount of shielding provided by the structure generally remained consistent for housing-units composed of thin, light materials (vinyl, wood, and stucco).…”
Section: Methodsmentioning
confidence: 99%
“…The primary weather barriers selected to define these housing-units are composed of either brick-or vinyl siding for the walls with asphalt shingles for the roof. Dickson et al (2014bDickson et al ( , 2015 developed 98 housingunit models of varying combinations of nine primary weather barriers; five representing exterior walls, four representing roofs. Findings demonstrated that despite differing primary weather barrier compositions, the amount of shielding provided by the structure generally remained consistent for housing-units composed of thin, light materials (vinyl, wood, and stucco).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, previous studies have only addressed external dose contributions from unfractionated environmental surfaces (e.g. by Meckbach et al 10 , 11 , Jacob and Meckbach 12 , Kis et al 13 , 14 , Salinas et al 15 , Dickson et al 16 , Dickson and Hamby 17 , and Hinrichsen and Andersson 18 ), such as the whole ground area. In contrast, we have applied the isodose concept to study the external dose contributions inside typical Northern European house models from contamination on the ground with a resolution of 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the transport code MCNP6 in determining exposure reduction for a modular building type has been experimentally verified in a previous study by our group . Further Monte Carlo simulations were performed for an industrial area (Kis et al 2003, Kis et al 2004, for various scenarios of U.S. residential structures (Dickson & Hamby 2014, Dickson & Hamby 2016, Dickson et al 2017, for typical houses in Brazil (Salinas et al 2006), and typical buildings in Japan (Furuta & Takahashi 2015). To the best of our knowledge such simulations have not previously been performed for buildings with glass facades that can be found in many cities now as a part of modern architecture or buildings with similar shielding properties.…”
Section: Introductionmentioning
confidence: 99%